Do the psychological benefits of greenspace depend on one's personality? - Ambrey, Christopher; Cartlidge, Nigel; Manning, M; Fleming, Christopher (My University, 2017)
Greenspace is thought to yield psychological benefits in terms of reducing stress and restoring attentional fatigue. The efficacy of exposure to greenspace may depend greatly on an individual's personality. Certain personality traits may make an individual more susceptible to experiencing stress and attentional fatigue and hence these same individuals may derive greater psychological benefits from greenspace than others. Employing data from the Household, Income and Labour Dynamics in Australia (HILDA) survey and Geographic Information Systems (GIS), this study investigates the extent to which one's personality traits may moderate the psychological benefits of greenspace. The results provide some evidence to suggest that individuals who report higher levels of emotional stability (equivalently, lower levels of neuroticism) glean noticeably greater psychological benefits from greenspace. This result may reflect more emotionally stable individuals being more likely to venture out and take pleasure in green and more hospitable spaces. Conversely, and in line with a priori expectations, there is some, albeit weak evidence, to suggest that individuals who report higher levels of conscientiousness realise greater psychological benefits from greenspace than those who report comparatively lower levels of conscientiousness. These findings extend on existing knowledge in the area of environmental psychology on the benefits of nature.
Personality and Individual Differences
Keywords: Health -- Wellbeing; Health -- Mental; Actvities -- Leisure and lifestyle; Health and wellbeing; Actvities; Health; Mental; Wellbeing; Leisure and lifestyle; Health and wellbeing